Combustion synthesis of ceramic nanoparticles for solid oxide fuel cells - Dong, Dehua; Li, Chun-Zhu; Wang, H. (John Wiley & Sons, Ltd, 2010)
Two combustion synthesis methods involving the use of polyacrylamide hydrogel and humic acids (HAs) as fuels were developed to synthesize ceramic nanoparticles for fabrication of solid oxide fuel cells (SOFCs). Using polyacrylamide hydrogel as fuel, highly crystalline NiO/Ce0.8Sm0.2O1.9 (SDC) and SDC nanoparticles were synthesized to make a modified layer and subsequent dense electrolyte film on the anode support. HA was used as complexible fuel to synthesize Sm0.5Sr0.5CoO3 nanoparticles for preparing the SOFC porous cathode. The single SOFCs made from these nanoparticles exhibited a maximum power density of 740 mW cm−2 at 650 °C operated with H2/air as fuel/oxidant, suggesting the synthesized nanoparticles are of high quality as SOFC materials.